(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
That the electronic payments system plays an important role in the effectiveness of commercial banks by attracting domestic or foreign investors, especially in the banking sector , It must keep abreast of global developments and technology in the field of banking that lead to the effectiveness of the bank by providing modern banking services and good customer service that improves the reputation of the bank, as well as develop its activities and promotes economic development at the country level , The technological progress of the bank will increase the speed of conducting banking operations, accuracy and safer , here should be laws and regulations related to electronic payment systems keep pace with the laws and regulations in the developing world as well as adapt to the evolving banking environment and that there should be a bank awareness among everyone and not to stay on the traditional banking methods.